COMPARATIVE ANALYSIS OF FIXED ASSETS ACCOUNTING IN THE LOGISTICS COMPLEX BY ISFO AND RSA - Andrey P. Garnov; Viktoriya Yu. Garnova (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article provides comparative analysis of provisions of the Russian accounting standards and international finance accounting  standards concerning fixed assets recording. The authors offer a new definition of fixed assets, which is based on similarity of definitions  according to ISFA and RA. The goals of accounting fixed assets were given. Conditions necessary to recognize the asset as an item  of fixed assets were described. Types of vale of fixed assets  according to RA 6/01 and ISFA were given and their comparative  analysis was made. Instructions concerning estimation of fixed  assets value were provided for different variants of their coming to  the organization: in case of depositing by founders to the authorized  capital, buying from manufacturers, independent manufacturing, obtaining through the donation contract, exchanging  to other property. The article pointed out to cases when balance value of fixed assets shall be altered and showed the procedure of fixed assets accounting from the moment of their putting into  operation. It underlined the idea that ISFA 16 and RSA 6/01 pay  serious attention to this problem but in different ways. Specific  features of fixed assets accounting in logistics complexes were described.